Self-Management Education for the Quality of Life of Patients with Pulmonary Tuberculosis - Setiyowati, Eppy; Hanik, Umi; Wardani, Erika Martining; Afandi, Mujad Didien; Juliasih, Ni Njoman (International Journal of Psychosocial Rehabilitation, 2020)
Treatment for pulmonary tuberculosis (TB) may become a problem when the patients show no adherence to the treatment and feel bored with its long duration. This condition may lead to drop out in the treatment. Therefore, this study aimed to analyze the effects of self-management education on the quality of life of patients with pulmonary TB. The design of this study was quasi-experimental, conducted in 3 Puskesmas (Perak Timur, Sawahan, Kebonsari), in which 150 respondents were divided into 2 groups: 75 respondents in the control group and 75 respondents in the treatment group. They were chosen as the sample by using a simple random sampling technique. The data were collected by conducting a pretest to identify the quality of life, interventions through self-management education, and finally providing a posttest. Furthermore, the data were analyzed using the Mann Whitney U test and Wilcoxon signed rank test. Change in the phsycal health domain, psychological domain, social domain and an enviroment domain that was effect self-management education the right place for the treatment is puskesmas, and a high hope for a cure needs supports from the family and medical workers. Self-management education increases the quality of life of patients with pulmonary TB. Future research is expected to analyze their life expectancy more deeply.